Draft Genome Sequence of Thalassospira xiamenensis Strain MCCC 1A03042(T) - Li, Meiqing (Genome Announc, 2017)
Thalassospira xiamenensis strain MCCC 1A03042(T) was isolated from deep-sea sediment of the Indian Ocean, and it was characterized with heavy-metal arsenic tolerance. Here, we present the draft genome of strain MCCC 1A03042(T), which contains 4,786,207 bp with a G+C content of 52.6% and 4,359 protein-coding genes.